Behavioral Rules of Officials according to Yeznik Koghbatsi - Mirzoyan, Valeri (Armenian Folia Anglistika, 2008)
The behavioral rules suggested by the great Armenian philosopher Yeznik Koghbatsi (380-450) can justly find their place in any collection of “aphorisms about rule and power”. He postulated advice, appeals, commandments, norms of behavior which can refer to everyone irrespective of their social position. Koghbatsi’s behavioral norms can be summed up in the following provisions:• Power is not a will to rule, rather it is an obligation.• The just official not only imposes his will on his subjects, but “rules like a loyal servant” and takes care of the latter.• To rule means displaying governing skills, i.e. guiding the subjects to the realization of the common goals.• If the official is loved by people, he must be content, if no, he must demonstrate patience and tenacity• The official must avoid false kindness and must be able to punish the one who is guilty• Reproach and rebuke must be well-grounded and if the subject has not accepted his guilt voluntarily, he must demonstrate tolerance• The subject must be reproached in private• When rebuking others, the official must not abuse his position, rather he must have moral grounds for that.• The most powerful lever of rule is the positive example of the official while the greatest harm is inflicted by his negative behavior• Everybody, be it an official or a subject, must be ready and willing to listen to advice.